Faktor-Faktor yang Berhubungan dengan Peran Usaha Mikro Kecil Menengah (UMKM) (Studi Kasus Pada Kelompok Pengrajin Tapis Mutiara di Kecamatan Negeri Katon Kabupaten Pesawaran) - Alda, Mareta Karunia; Yanfika, Helvi; Listiana, Indah; Nurmayasari, Indah (Suluh Pembangunan : Journal of Extension and Development, 2024)
UMKM activity is one of the activities in the business sector that can be developed and has a consistent nature in the national economy. The purpose of this study was to determine the factors related to the role of Tapis Mutiara UMKM and to find out the acceptance of members of the Tapis Mutiara UMKM group in Negeri Katon District, Pesawaran Regency. This research was conducted in the District of Negeri Katon, Pesawaran Regency in November-December 2021. The respondents were 33 Tapis craftsmen who were members of the Pearl Tapis craftsman group in the Negeri Katon District of Pesawaran Regency. This research uses a case study method, namely a quantitative descriptive approach. The results showed the acquisition of Tapis Mutiara member acceptance within one year and the factors that were significantly related to the role of the Tapis Mutiara craftsman group in the Negeri Katon District, Pesawaran Regency, namely internal factors consisting of leadership ability, communication patterns and group atmosphere, while the internal factors consisted of leadership skills, communication patterns and group atmosphere. external, namely the existence of guidance, access to assistance for raw materials for filter products and the use of technology in product sales. Keywords: UMKM, the Role of UMKM, Membership Acceptance